2016
DOI: 10.2298/pan130515024y
|View full text |Cite
|
Sign up to set email alerts
|

Globalization, economic freedom, and wage inequality: A panel data analysis

Abstract: This paper examines the impact of globalization and liberalization on wage inequality using the KOF globalization index, the Economic Freedom Index (EFI) of the Fraser Institute and the Theil industrial pay inequality statistic compiled by the University of Texas Inequality Project (UTIP). Both static and dynamic fixedeffects models are estimated using a 5-year panel data set consisting of about 90 developed and developing countries for the 1970-2005 period. Estimation results from the dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Tsai (2007) reveals the affirmative effect of political globalisation on human welfare. The results of Yay et al (2016) from fixed-effects estimations show that political globalisation measured by the KOF index has an affirmative impact on wage inequality. Bergh and Nilsson (2010) found that political globalisation does not increase inequality.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Tsai (2007) reveals the affirmative effect of political globalisation on human welfare. The results of Yay et al (2016) from fixed-effects estimations show that political globalisation measured by the KOF index has an affirmative impact on wage inequality. Bergh and Nilsson (2010) found that political globalisation does not increase inequality.…”
Section: Literature Reviewmentioning
confidence: 96%
“…However, it conceals the change in skill composition of workers, which is crucial to understanding the change in “skill premium” over time. Despite the limitations of the traditional theorem for further analyses on widening income inequality in developing economies, Yay, Taştan, and Oktayer (2016): 583) use several approaches to clarify the global rise in the skill premium such as purchasing‐power differences, outsourcing, differences in goods prices and factor returns, high technology transfers, and foreign direct investment. First, trade specialization may not be beneficial for poor countries because their purchasing‐power differs significantly from rich countries in that the demand for the goods is different between those countries.…”
Section: Channels Of Influencementioning
confidence: 99%
“…However, this may not be the case when the labor markets are subjected to rigidities among domestic markets (Goldberg & Pavcnik, 2007). Additionally, besides the current problems in labor markets, there may be other factors which restrict to reach an optimal point in the economy and lead to prices and wages to change over time (Yay et al., 2016: 583).…”
Section: Channels Of Influencementioning
confidence: 99%